Enhanced therapeutic effect using sequential administration of antigenically distinct oncolytic viruses expressing oncostatin M in a Syrian hamster orthotopic pancreatic cancer model. Issue 1 (December 2015) - Nistal-Villan, Estanislao; Bunuales, Maria; Poutou, Joanna; Gonzalez-Aparicio, Manuela; Bravo-Perez, Carlos; Quetglas, Jose; Carte, Beatriz; Gonzalez-Aseguinolaza, Gloria; Prieto, Jesus; Larrea, Esther; Hernandez-Alcoceba, Ruben
Abstract Background The limited efficacy of current treatments against pancreatic cancer has prompted the search of new alternatives such as virotherapy. Activation of the immune response against cancer cells is emerging as one of the main mechanisms of action of oncolytic viruses (OV). Direct oncolysis releases tumor antigens, and viral replication within the tumor microenvironment is a potent danger signal. Arming OV with immunostimulatory transgenes further enhances their therapeutic effect. However, standard virotherapy protocols do not take full advantage of OV as cancer vaccines because repeated viral administrations may polarize immune responses against strong viral antigens, and the rapid onset of neutralizing antibodies limits the efficacy of redosing. An alternative paradigm based on sequential combination of antigenically distinct OV has been recently proposed. Methods We have developed a protocol consisting of sequential intratumor administrations of new Adenovirus (Ad) and Newcastle Disease Virus (NDV)-based OV encoding the immunostimulatory cytokine oncostatin M (OSM). Transgene expression, toxicity and antitumor effect were evaluated using an aggressive orthotopic pancreatic cancer model in Syrian hamsters, which are sensitive to OSM and permissive for replication of both OVs. Results NDV-OSM was more cytolytic, whereas Ad-OSM caused higher OSM expression in vivo. Both viruses achieved only a marginal antitumor effect in monotherapy. In addition, strong secretion of OSM in serum limited the maximal tolerated dose of Ad-OSM. In contrast, moderate doses of Ad-OSM followed one week later by NDV-OSM were safe, showed a significant antitumor effect and stimulated immune responses against cancer cells. Similar efficacy was observed when the order of virus administrations was reversed. Conclusion Sequential administration of oncolytic Ad and NDV encoding OSM is a promising approach against pancreatic cancer.